Modelling formation and development of longitudinal cracks in concrete crossing corroding reinforcement - Jokūbaitis, Vidmantas; Jurkša, Arvydas (Journal of Civil Engineering and Management, 2002)
Tensile stresses in concrete occur under the action of reinforcement rust pressure. When they exceed concrete tensile strength or concrete extension strain exceeds limit value, concrete cracks. Physical and numerical models of such cracks are proposed for analysis of formation and development based on the main assumption that in the place of the rusting bar there is an artificial cut of circular shape, the contour of which is subjected to a pressure, imitating pressure of rust. Limit pressure values and character of formation and development of cracks through concrete cover to reinforcement are compared with data of experimental investigations performed by S. Williamson. The analysis has indicated that proposed models of formation and development of longitudinal concrete cracks are based on correct assumptions and can be applied for assessing the state of cracked reinforced concrete structures. Frist Published Online: 30 Jul 2012